Experimental Investigation of Producing Brown's Gas using a Metal‐Plate Electrolyzer for Diesel Vehicle Applications. Issue 2 (12th August 2016) - Wu, Yimin; Xie, Changjun; Burke, Andrew; Zhao, Hengbing; Miller, Marshall; Warner, Stan
Abstract: The infusion of Brown's gas into a diesel engine can create faster, more efficient combustion, which can be produced by using an alkaline electrolyzer. Brown's gas consists of 2/3 hydrogen and 1/3 oxygen by volume, as produced by the alkaline electrolyzer. An experimental test setup for verifying the performance of an electrolyzer provided by Stan Warner was established in the Battery Laboratory at the University of California Davis. A series of tests were performed under constant current and pulse current modes. Analyses of the data indicate that the electrolyzer functions reliably at all current values. The Brown's gas production rate is found to be linear with current and in agreement with Faraday's Law. The electrolyzer meets the developer's claim of 3–4 L min −1 of Brown's gas production at 60 A. The calculated energy efficiency of the electrolyzer based on the high heating value of hydrogen is 61 % at 70 A. The performance and pulse characteristics of the Warner electrolyzer indicate it is well suited for use in diesel truck applications. Abstract : Green chemistry with Brown′s gas : An experimental test bench is established in the Battery Laboratory at the University of California‐Davis for verifying the performance of an electrolyzer in diesel engine applications. A series of tests are performed under constant current and pulse current modes. The Brown's gas (2/3 hydrogen and 1/3 oxygen by volume) production rate is found to be linear with current and in agreement with Faraday's Law. The performance and pulse characteristics of the Warner electrolyzer indicate it is well suited for use in the diesel truck applications.